OrganIzación espacial y estructura de una población de Ionopsis utricularioides (Orchidaceae) en un área suburbana de Pinar del río, Cuba - Gacía González, Alfredo; Riverón Giró, Frander (Lankesteriana: International Journal on Orchidology, 2014)
We determined the population structure and some habitat conditions of a Ionopsis utricularioides (Orchidaceae) population in an orange orchard (citrus sinensis, Rutaceae), located in the “La Juanita” farm, Pinar del Río, Cuba. We took into account all the orange trees of the orchard, and located all the individuals of I. utricularioides. The following variables were analyzed: height and diameter of branches in growing orchids, orchid distribution on phorophytes (trunk, branches or twigs), life stage of the orchids (immature or adults), orientation of orchids in the phorophyte, if the plants were solitary or aggregated, and kind of neighbours in the case of the aggregate. Of the 10 trees of c. sinensis, eight trees had orchids of I. utricularioides, with 217 plants. Almost all orchids were observed on the twigs (98.61 %) and none were observed on the trunk of the tree. The number of plants is relatively high in the two stage of life. Most plants of I. utricularioides were found growing aggregate with individuals of the same species, or with other species of vascular epiphytes. This is a stable and mature population. Growing up in aggregation can give competitive advantages to I. utricularioides.